MUATAN KURIKULUM PENDIDIKAN PERSPEKTIF AL-QUR’AN DAN AL-HADIT - Noer, Mohammad Fahrudi; Alawy, Naufal (LP2M Sekolah Tinggi Agama Islam Ar-Rosyid Surabaya, 2024)
Abstract This article explains the concept of the curriculum which is reviewed from the perspective of several verses from the Qur'an and al-Hadith. This article is written with a literature study method that has primary references such as the book of tafsir al-Munir, tafsir Jalalain, and tafsir al-Mishbah and also secondary references such as printed books and journals that have been indexed by SINTA. The findings are that a curriculum must be holistic which includes cognitive, affective, and psychomotor. The curriculum must also have a consciousness nature. Because this is the source of education problems in Indonesia. The curriculum should also consist of aspects of faith, moral, intellectual, social, psychological, and so on. .